Flexural behaviour of room-sized precast lightweight large concrete sandwich roof panels - Prabhakar, J.; Lakshmikandhan, K.N.; Saravanakumar, K. (Journal of Structural Engineering, 2024)
Rapid population growth, urbanization and shortage of conventional construction materials are delaying infrastructuredevelopment. Labor shortages in conventional construction practices widen the gap between demand and supply of residential units. The precast lightweight panel construction can be a feasible solution for the above problems, Inparticularly, needs focused research towards the development of wall and the roof components, which are the major parts of building construction both interms of material and budget requirements. Limited research work is carriedout on precast lightweight large wall panels and one way roof slab panels. Usage of one-way slab panel is not fully accepted by the construction industry due to its complication in leak proof in between the one-way slab and hence, itis presently managed with in-situ two-way slab construction. Considering the above, The present paper investigates room-sized large lightweight roof panels for two-way slab applications. The roof panel is fabricated using the standard,market available expanded polystyrene (EPS) panels of size 1200 mm x 3000 mm x 100 mm is suitably modified to a size of 3000mm x 3000mm x 100mm, and then sandwiched using 25 mm thick M40 grade concrete ferrocement wythesarround the EPS panel. Considering the requirement of UDL load applications, a novel 12-point loading mechanism is devised for simulating equivalent uniformly distributed conditions, for studying its two-way flexural behavior. Anonlinear finite element analysis is performed numerically for ascertaining the performance of the panel for both udl and 12-point loading cases, and the results are found comparable. The strain gauges are pasted in both steel andconcrete portions and placed LVDTs to observe the deflected pattern. The panel first cracked at a load of about 91 kN which is equivalent to the UDL distribution is 10.11 kN/m². The first crack load is found well beyond the factoreddesign load in a normal residential building, which is about 1.7 times lesser. The panel reached its ultimate load when it reaches 195 kN. The experimental results are compared with numerical results and found comparable with lesser than 10% variations untill the slab starts cracking. After cracking, the experimental results shows excessive deformation compared to the analytical results due to the support uncertainaties. From the deflected shape and the crack pattern shows a typical two-way slab action. The sandwich roof panel is outperformed and exhibited better performance which is more beneficial for the precast industry.